IMMU-40. KINETICS OF DEXAMETHASONE-INDUCED ALTERATIONS OF DIVERSE IMMUNE SUBSETS IN VIVO. (14th November 2022) - Yaghi, Nasser; Watanabe, Masashi; Watowich, Matthew; Li, Aiguo; Briceno, Nicole; Yaghi, Omar; Livak, Ferenc; Siddiqui, Shafiuddin; Wolcott, Karen; Zhang, Wei; Zhang, Meili; Song, Hua; et al.
Abstract: INTRODUCTION: Immune therapeutic strategies are ideal for exploiting glial tumor heterogeneity. A limitation to their implementation for intra-axial brain tumors has been corticosteroids. Steroid use is associated with worse progression-free and overall survival when combined with some immunotherapies. Dexamethasone remains first line treatment for vasogenic cerebral edema and a primary therapy for immune-related adverse events secondary to immunotherapies. While used for decades, steroid immunosuppressive effects remain insufficiently characterized. We examined the temporal effects of dexamethasone on an extensive repertoire of immune cell subtypes. METHODS: Non-tumor bearing C57BL/6 mice were treated with a onetime dose of 1 mg/kg dexamethasone via gavage, and peripheral blood was sampled at timepoints spanning 1 hour to 7 days. Flow cytometry was performed in triplicate to determine absolute cell counts of circulating B cells, CD8 + T cells (naive/memory), CD4 + T cells (naive/memory/regulatory), NK cells, neutrophils, monocytes, and eosinophils at each timepoint. We examined T cell function at multiple timepoints using an anti-CD3/CD28 bead stimulation assay. RESULTS: At 1-hour post-treatment, cell counts across lymphoid subtypes increased. Neutrophils dramatically increased, while the remaining myeloid subtypes began to decrease. NK cells, similarly, were decreased in number. At 4-hours post-treatment all immune subtypes had their lowest circulating counts. There were corresponding increases in CD8 + and CD4 + T cell expansion and proliferation indices at 4-hours. By 24-hours post-treatment, all immune subtypes had recovered to or surpassed pre-treatment counts, except monocytes. By 7 days, the Tregs increased to 186% of pre-treatment counts, the highest of all subtypes, while eosinophils, monocytes, and NK cells never fully recovered to their pre-treatment baselines. CONCLUSIONS: Understanding dexamethasone influence on circulating immune cells will inform optimal treatment timing for immunotherapies in brain tumor patients. We are further characterizing transcriptomic changes within immune cell subtypes following dexamethasone administration via population-level RNA sequencing over time.